Discovery and quantification of proteins of biological relevance through differential proteomics and biosensing - Lonardoni, Francesco (Cranfield University, 2012)
Medical diagnosis is the process of attempting to determine and/or identify a possible disease or disorder. This process is revealed by biomarkers, defined by The Food and Drug Administration (FDA) as “characteristics that are objectively measured and evaluated as indicators of normal biologic processes, pathogenic processes, or pharmacologic responses to a therapeutic intervention”. The process of biomarker discovery has been boosted in the last years by proteomics, a research discipline that takes a snapshot of the entire wealth of proteins in an organism/ tissue/ cell/ body fluid. An implementation of the analysis methods can help in isolate proteins present in the low range of concentrations, such as biomarkers very often are. An established biomarker can further be measured with the help of biosensors, devices that can be employed in the point-of care diagnostics. This PhD thesis shows and discusses the results of three projects in the field of protein biomarkers discovery and quantification. The first project exploited proteomics techniques to find relevant protein markers for Intrauterine Growth Restriction (IUGR) in cordonal blood serum (UCS) and amniotic fluid (AF). A 14 proteins in UCS and 11 in AF were successfully identified and found to be differentially expressed. Molecularly Imprinted Polymers (MIPs) directed towards proteins and peptides containing phosphotyrosine were then produced, with the final goal of selectively extracting phosphopeptides from a peptide mixture. An alteration of the phosphorylation pattern is in fact often associated to important diseases such as cancer. The polymers were produced as nanoparticles, that were characterised with Dynamic Light Scattering (DLS) and Atomic Force Microscopy (AFM). A recipe was also tested for binding capacity towards phosphotyrosine. A Surface Plasmon Resonance (SPR) biosensor to quantify hepcidin hormone was finally produced. This is the major subject in iron homeostasis in vertebrates and marker of iron unbalance diseases. A calibration curve was made and affinity/kinetic parameters for the ligand employed were measured.
Keywords: IUGR; 2D-PAGE; phosphoproteomics; MIPs; nanoparticles; hepcidin; biosensors